Functions and Reasons for the Published of Notice of Tax Assessment (SKP) and Notice of Tax Collection (STP) based on the General Provisions and Tax Procedures Law (KUP) - kesia atira simanjuntak; Jelita Miguela Da Silva Martins; Try Liani; Galuh Tresna Murti (Jurnal Riset Perpajakan: Amnesty, 2023)
This study aims to explain the functions and reasons for the issuance of Notice of Tax Assessment (SKP), Notice of Tax Underpayment Assessment (SKPKB), Notice of Additional Tax Underpayment Assessment (SKPKBT), Notice of Overpayment Assessment (SKPLB), Notice of Nil Tax Assessment (SKPN) and Notice of Tax Collection (STP) based on the Law on  General Provisions and Tax Procedures (KUP). Because there are still many taxpayers who do not understand why these letters were issued and many still do not know what their function is. This study uses a qualitative approach. Data collection is done through analysis, data collection, and drawing conclusions. The results of this study indicate that all types of SKP and STP are issued because there are taxpayers who report that their tax bills have been overpaid, and there are also those who, when examined, show that there is an underpayment and there are also those who do not have the amount of tax owed. And based on the results of research Tax Collection Letters are issued to make tax bills and make bills for sanction fees in the form of fines or interest.